2021
DOI: 10.3390/nu13082809
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Obesity Effects of Lemon Fermented Products in 3T3-L1 Preadipocytes and in a Rat Model with High-Calorie Diet-Induced Obesity

Abstract: Lemon (Citrus limon) has antioxidant, immunoregulatory, and blood lipid-lowering properties. This study aimed to determine the effect of the lemon fermented product (LFP) which is lemon fermented with Lactobacillus OPC1 to prevent obesity. The inhibition of lipid accumulation in 3T3-L1 adipocytes is examined using a Wistar rat model fed a high-fat diet to verify the anti-obesity efficacy and mechanism of LFP. Here, it was observed that LFP reduced cell proliferation and inhibited the lipid accumulation (8.3%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
(50 reference statements)
0
18
0
Order By: Relevance
“…Furthermore, SCD and DBI (also named ACBP) are also main the members of PPARγ signaling pathway, which is responsible for fatty acid desaturation (Stoeckman and Towle, 2002 ; Neess et al, 2006 ). Meanwhile, besides the gene of PPARγ signaling pathway, other fatty acid-related genes, such as FASN, HSD17B12, ELOVL2 , and ELOVL6 , are also involved in lipid metabolism (Hachim et al, 2020 ; Maycotte-Cervantes et al, 2020 ; Wu et al, 2021 ). These data indicated that PFF might contribute to attenuate fatty acid synthesis, lipid generation, and accelerate the lipid metabolism to control hepatic lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, SCD and DBI (also named ACBP) are also main the members of PPARγ signaling pathway, which is responsible for fatty acid desaturation (Stoeckman and Towle, 2002 ; Neess et al, 2006 ). Meanwhile, besides the gene of PPARγ signaling pathway, other fatty acid-related genes, such as FASN, HSD17B12, ELOVL2 , and ELOVL6 , are also involved in lipid metabolism (Hachim et al, 2020 ; Maycotte-Cervantes et al, 2020 ; Wu et al, 2021 ). These data indicated that PFF might contribute to attenuate fatty acid synthesis, lipid generation, and accelerate the lipid metabolism to control hepatic lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Fermented products, which provided live microbial, have been commonly applied in the human and poultry industry (Li et al, 2020 ; Park et al, 2021 ; Wu et al, 2021 ; Lv et al, 2022 ). Rice bran fermented by Weissella koreensis DB1 can decrease the serum levels of triglyceride (TG) and total cholesterol (TC) and significantly downregulate the hepatic gene expression of C/EBP, SREBP-1c, FAS, and ACC in mice (Park et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lemon is known to have antioxidant activity, and lemon fermented product (LFP) at 0.75 and 1 mg/mL for 10 days was reported to inhibit the accumulation of lipids by 8.3% in 3T3L1 adipocytes. In addition, based on in vivo studies using mice, LFP at a dose of 2.89 g/kg for 9 weeks can reduce the body weight of obese mice by 9.7%, decrease triglyceride levels (17.0%), glucose (29.3%) and free fatty acids (17.9%) and can increase serum HDL (17.6%) [71].…”
Section: Other Antioxidantsmentioning
confidence: 99%
“…EOs have many biological properties, including antioxidant activity from having redox properties, allowing them to neutralize free radicals, and anti-inflammatory, by inhibiting the release of histamine and the activation of inflammatory mediators [ 11 , 12 , 13 , 14 ]. Recently, the effects of some compounds present in medicinal plants on adipocytes have been evaluated with a favorable effect on these cells [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], adipocyte number, and oxidative stress [ 28 , 29 , 30 , 31 ]. Moreover, recent data indicate that aqueous extracts of some EOs could improve metabolic alterations [ 15 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these plants have been shown to have antidiabetic, antioxidant, and anti-inflammatory properties [ 3 , 6 , 10 , 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], including Lippia spp, which has been confirmed in previous studies to influence adipocyte functionality by decreasing lipogenesis, reversing the hypertrophic state, and generating changes in lipolysis and adipogenesis [ 33 ]. Specifically, Lippia citriodora showed an effect on some important genes in adipogenesis (CCAAT/enhancer-binding protein Alpha ( Cebpa) and Peroxisome Proliferator- activated receptor gamma ( Pparg )) and, therefore, modifies lipid accumulation, decreases adipocyte hypertrophy, and affects adipokine release after treatment for 48 h at concentrations of 50 to 400 µg/mL in 3T3-L1 adipocytes [ 33 ].…”
Section: Introductionmentioning
confidence: 99%